Body iron status and gastric cancer risk in the EURGAST study. Issue 12 (16th July 2015) - Fonseca‐Nunes, Ana; Agudo, Antonio; Aranda, Núria; Arija, Victoria; Cross, Amanda J.; Molina, Esther; Sanchez, Maria Jose; Bueno‐de‐Mesquita, H. B(as); Siersema, Peter; Weiderpass, Elisabete; Krogh, Vittorio; Mattiello, Amalia; et al.
<x xml:space="preserve">Abstract</x> Although it appears biologically plausible for iron to be associated with gastric carcinogenesis, the evidence is insufficient to lead to any conclusions. To further investigate the relationship between body iron status and gastric cancer risk, we conducted a nested case–control study in the multicentric European Prospective Investigation into Cancer and Nutrition (EPIC) study. The study included 456 primary incident gastric adenocarcinoma cases and 900 matched controls that occurred during an average of 11 years of follow‐up. We measured prediagnostic serum iron, ferritin, transferrin and C‐reactive protein, and further estimated total iron‐binding capacity (TIBC) and transferrin saturation (TS). Odds ratios (ORs) and 95% confidence intervals (CIs) for the risk of gastric cancer by iron metrics were estimated from multivariable conditional logistic regression models. After adjusting for relevant confounders, we observed a statistically significant inverse association between gastric cancer and ferritin and TS indices (ORlog2 = 0.80, 95% CI = 0.72–0.88; OR10%increment = 0.87, 95% CI = 0.78–0.97, respectively). These associations appear to be restricted to noncardia gastric cancer (ferritin showed a p for heterogeneity = 0.04 and TS had a p for heterogeneity = 0.02), and no differences were found by histological type. TIBC increased risk of overall gastric cancer (OR50 µg/dl = 1.13, 95% CI = 1.02–1.2) and also with noncardia gastric cancer (p for heterogeneity = 0.04). Additional analysis suggests that time between blood draw and gastric cancer diagnosis could modify these findings. In conclusion, our results showed a decreased risk of gastric cancer related to higher body iron stores as measured by serum iron and ferritin. Further investigation is needed to clarify the role of iron in gastric carcinogenesis.